2018
DOI: 10.4081/ija.2018.1136
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic amendments on nitrate leaching mitigation in a sandy loam soil of Shkodra district, Albania

Abstract: European lacustrine systems are frequently exposed to nitrate (NO3–) pollution causing eutrophication processes. An example of these lakes is Shkodra Lake, a large, shallow lake shared by Albania and Montenegro, in the Balkans Peninsula. Shkodra Lake is a natural sink that collects NO3– from agricultural activities, widely diffused in the surrounding area. The additions of wheat straw and biochar have been suggested to increase soil NO3– retention of agricultural lands. To better understand the role of these t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 46 publications
(52 reference statements)
0
13
0
1
Order By: Relevance
“…On the contrary, biochar addition to the soil reduced NO 3 − content in Swiss chard leaves, likely due to the occurrence of a nitrate sorption on biochar surface. Several authors showed that biochar is effective in retaining nitrates in the soil [60][61][62][63][64][65] and attributed this ability to the high pyrolysis temperature (>600 • C) at which the biochar is obtained [66]. According to the literature, the biochar nitrate retention we hypothesized in our experiment could be explained considering the high temperature (650 • C) applied to vine pruning residues for biochar production.…”
Section: Total Nitrogen and Nitrate Leaf Contentmentioning
confidence: 61%
“…On the contrary, biochar addition to the soil reduced NO 3 − content in Swiss chard leaves, likely due to the occurrence of a nitrate sorption on biochar surface. Several authors showed that biochar is effective in retaining nitrates in the soil [60][61][62][63][64][65] and attributed this ability to the high pyrolysis temperature (>600 • C) at which the biochar is obtained [66]. According to the literature, the biochar nitrate retention we hypothesized in our experiment could be explained considering the high temperature (650 • C) applied to vine pruning residues for biochar production.…”
Section: Total Nitrogen and Nitrate Leaf Contentmentioning
confidence: 61%
“…As an alternative to mineral fertilization, there is currently a growing interest in exploring the benefits and opportunities as well as the limitations in the use of organic amendments, as compost and biochar, to enhance plant nutrition, crop yield and quality, protect soil fertility, and ensure environmental sustainability of crop production [13][14][15][16][17]. Compost is the product of organic waste stabilization and sanitation through aerobic decomposition process, under controlled conditions [13].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies indicated the ability of biochar to retain anions although the underlying mechanisms are not always clear. A number of experiments [18][19][20][21][22][23][24] showed that biochar is an effective option in mitigating nitrate leaching. Agegnehu et al [25] founded that biochar reduced leaching of, P, NO 3 − -N, NH 4 + -N, K, Ca, Mg, and Na.…”
Section: Introductionmentioning
confidence: 99%